Simulation-based training for ICU nurses: a crucial investment - Rai, Neha (International Journal Of Community Medicine And Public Health, 2025)
The evolving complexity of critical care settings has placed increased demands on nursing professionals, particularly those working in Intensive Care Units (ICUs). In this context, I would like to highlight the urgent need to integrate simulation-based training as a core component of ICU nurse education and professional development in India. Simulation offers a safe, reproducible, and learner-centric approach to mastering essential clinical competencies, and is no longer a luxury but a necessity in modern healthcare education.